Seeking Care: Youth’s Counterstories Within the Context of Mental Health (LEARNing Landscapes, 2024)
In this article, we draw on a narrative inquiry into the experiences of children, youth, and families waiting for mental health support during the COVID-19 pandemic in Western Canada. We foreground two youths’ experiences (Gillian, who self-identifies as transgender, and Malek, who self-identifies as racialized) to highlight the complex barriers and supports each encountered while attempting to secure appropriate care as they navigated moments of crisis within their worlds of home, school, and communities. By inquiring into their mental health stories, we foreground the unique ways these youth enacted counterstories to disrupt hegemonic constructions of their identities, build agency, and support their wellbeing.
Keywords: COVID-19; narrative inquiry; racialized; youth mental health; 2SLGBTQ